Climate change impacts flowering phenology in Gongga Mountains, Southwest China - Zu, Kuiling; Chen, Fusheng; Li, Yaoqi; Shrestha, Nawal; Fang, Xiangmin; Ahmad, Shahid; Nabi, Ghulam; Wang, Zhiheng (Plant Diversity, 2023)
Flowering phenology of plants, which is important for reproductive growth, has been shown to be influenced by climate change. Understanding how flowering phenology responds to climate change and exploring the variation of this response across plant groups can help predict structural and functional changes in plant communities in response to ongoing climate change. Here, we used long-term collections of 33 flowering plant species from the Gongga Mountains (Mt. Gongga hereafter), a biodiversity hotspot, to investigate how plant flowering phenology changed over the past 70 years in response to climate change. We found that mean flowering times in Mt. Gongga were delayed in all vegetation types and elevations over the last 70 years. Furthermore, flowering time was delayed more in lowlands than at high elevations. Interestingly, we observed that spring-flowering plants show earlier flowering times whereas summer/autumn plants show delayed flowering times. Non-synchronous flowering phenology across species was mainly driven by changes in temperature and precipitation. We also found that the flowering phenology of 78.8% plant species was delayed in response to warming temperatures. Our findings also indicate that the magnitude and direction of variation in plant flowering times vary significantly among species along elevation gradients. Shifts in flowering time might cause trophic mismatches with co-occurring and related species, affecting both forest ecosystem structure and function.
Keywords: Changes in flowering phenology; Elevation; Functional trait; Mountains; Plant communities